Structural response of steel-fiber-reinforced concrete beams under various loading rates. (1st February 2018) - Lee, Jin-Young; Shin, Hyun-Oh; Yoo, Doo-Yeol; Yoon, Young-Soo
Highlights: Static, impact, and blast tests were performed on identical RC beams. The use of steel fibers enhances ductility of RC beams regardless of strain rate. The fiber contribution to shear resistance was evaluated under various loading type. The static shear strength of SFRC beams were effectively predicted. The critical content of steel fiber varies according to strain rate and loading type. Abstract: This study presents the rate-dependent structural behavior of reinforced concrete (RC) beams with and without steel fibers and stirrups. Three different loading rates, i.e., quasi-static, impact, and blast loading, were adopted, and three different volume fractions (vf ) of hooked steel fibers, i.e., 0, 0.5, and 1%, were considered. The test results indicate that the addition of steel fibers enhanced the static, impact, and blast resistances of the RC beams in terms of higher load carrying capacity, higher energy absorption capacity, and lower maximum and residual displacements. However, the inclusion of 0.5 and 1 vol% steel fibers was insufficient to prevent brittle shear failure of the RC beams without stirrups. On the other hand, brittle shear failure was effectively prevented by incorporating stirrups. The beams including both 0.5 vol% steel fibers and stirrups demonstrated the highest performance, regardless of the strain rate in all the three loading conditions. Lastly, the static shear strengths of reinforced steel-fiber-reinforced concrete beams were effectively predicted based on Aoude's model, and the effectiveness of using steel fibers was greatest under the static loading condition, as compared with impact and blast loading conditions.